Sexual Dimorphic Responses in Lymphocytes of Healthy Individuals after Carica papaya Consumption - Jumat, Nur Ramziahrazanah; Chong, Mun Yee; Seman, Zainina; Jamaluddin, Rosita; Wong, Nyet Kui; Abdullah, Maha (Frontiers in Immunology, 2017)
Sexual dimorphism in immune response is widely recognized, but few human studies have observed this distinction. Food with endo-immunomodulatory potential may reveal novel sex-biased in vivo interactions. Immunomodulatory effects of Carica papaya were compared between healthy male and female individuals. Volunteers were given fixed meals supplemented with papaya for two days. Changes in blood immune profiles and hormone levels were determined. In females, total natural killer (NK) cell percentages decreased (12.7+4.4% vs 14.6+5.8%, p=0.018, n=18) while B cells increased (15.2+5.5 vs 14.5+5.0, p=0.037, n=18) after papaya consumption. Increased 17β-estradiol (511.1+579.7 pmol/l vs 282.7+165.0 pmol/l, p=0.036, n=9) observed in females may be crucial to this change. Differentiation markers (CD45RA, CD69, CD25) analysed on lymphocytes showed naïve (CD45RA+) non-CD4+ lymphocytes were reduced in females (40.7+8.1% vs 46.8+5.4%, p=0.012, n=8) but not males. A general suppressive effect of papaya on CD69+ cells, and higher percentage of CD69+ populations in females and non-CD4 lymphocytes, may be relevant. CD107a+ NK cells were significantly increased in males (16.8+7.0 vs 14.7+4.8, p=0.038, n=9) but not females. Effect in females may be disrupted by the action of progesterone which was significantly correlated with this population (R=0.771, p=0.025, n=8) after papaya consumption. In males, total T helper cells were increased (33.4+6.4% vs 32.4+6.1%, p=0.040, n=15). Strong significant negative correlation between testosterone and CD25+ CD4+ lymphocytes, may play a role in the lower total CD4+ T cells reported in males. Thus, dissimilar immune profiles were elicited in the sexes after papaya consumption and may have sex hormone influence.